The relationship of parent-child attachment and religiosity to improving adolescent self-esteem - Rachman, Yane Ardian; Sumarwan, Ujang; Latifah, Melly; Herawati, Tin (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
Adolescence is risky and vulnerable; the emergence of risky behavior is often motivated by low self-esteem. This study aims to analyze the effect of parental attachment and religiosity on the adolescents' self-esteem in Bogor City and the differences in parental attachment, religiosity, and self-esteem between male and female adolescents. This study uses an explanatory research design and aims to explain the cause-and-effect relationship between variables. This research has passed the ethical review of the Human Research Ethics Committee of the Bogor Agricultural University, with Number 1062/IT3.KEPMSM-IPB/SK/2023.The research was conducted in ten schools, namely four junior high schools and six senior high schools in Bogor City. The population of this study was adolescents in Bogor City. The sampling technique in this study was cluster random sampling based on class, involving ten schools with details of four junior high schools and six senior high schools, with 50 students from each school, so the total number of respondents was 500 respondents. The research was conducted in October 2023. Data analysis used Statistical Package for Social Science (SPSS) 25.0 for inferential analysis (independent sample T-Test and Structural Equation Modeling-Partial Least Square (SEM-PLS) for influence analysis. This study shows that adolescent self-esteem is influenced by parent-child attachment and religiosity. The difference in test results showed that religiosity in female adolescents was higher. Meanwhile, male adolescents have higher self-esteem. The implications of this research are the government can expand access to family and adolescent counseling services in schools and the community. This counseling can help families build better attachments, help adolescents find their identity, and improve their self-esteem.